Crystal structure of bis{μ(2)-2,2′-[(4,10-dimethyl-1,4,7,10-tetraazacyclododecane-1,7-diyl)bis(methylene)]bis(4-oxo-4H-pyran-3-olato)}dicobaltcalcium bis(perchlorate) 1.36-hydrate - Rossi, Patrizia (Acta Crystallogr E Crystallogr Commun, 2017)
The title compound, [CaCo(2)(C(22)H(30)N(4)O(6))(2)](ClO(4))(2)·1.36H(2)O or {Ca[Co(H(–2) L1)](2)}·2ClO(4)·1.36H(2)O {where L1 is 4,10-bis[(3-hydroxy-4-pyron-2-yl)methyl]-1,7-dimethyl-1,4,7,10-tetraazacyclododecane}, is a trinuclear complex whose asymmetric unit comprises a quarter of the {Ca[Co(H(–2) L1)](2)}(2+) trinuclear complex, half of a perchlorate ion and 0.34-water molecules. In the neutral [Co(H(–2) L1)] moiety, the cobalt ion is hexacoordinated in a trigonal–prismatic fashion by the surrounding N(4)O(2) donor set. A Ca(2+) cation holds together two neutral [Co(H(–2) L1)] moieties and is octacoordinated in a distorted trigonal–dodecahedral fashion by the surrounding O atoms belonging to the deprotonated oxide and carbonyl groups of two [Co(H(–2) L1)] units. The coordination of the Co(II) cation preorganizes L1 and an electron-rich area forms, which is able to host hard metal ions. The comparison between the present structure and the previously published ones suggests a high versatility of this ligand; indeed, hard metal ions with different nature and dimensions lead to complexes having different stoichiometry (mono- and dinuclear monomers and trinuclear dimers) or even a polymeric structure. The heterotrinuclear Co(II)–Ca(II)–Co(II) complexes are connected in three dimensions via weak C—H⋯O hydrogen bonds, which are also responsible for the interactions with the perchlorate anions and the lattice water molecules. The perchlorate anion is disordered about a twofold rotation axis and was refined giving the two positions a fixed occupancy factor of 0.5. The crystal studied was refined as a two-component inversion twin [BASF parameter = 0.14 (4)].